2015
DOI: 10.1016/j.acmx.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hypotension in the elderly: Findings in a Mexican population

Abstract: Post-prandial hypotension is a common finding in this elderly population. We did not find distinctive conditions or markers that allow identification of subjects at risk for postprandial hypotension and its complications. This should prompt for routine screenings in specialized facilities to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…The included studies were conducted in the following countries: South Korea [ 23 , 24 ], France [ 25 , 26 ], Australia [ 27 , 28 ], Japan [ 9 , 29 ], the USA [ 30 , 31 ], Belgium [ 10 ], Mexico [ 11 ] and the Netherlands [ 14 ]. Papers were published between 1991 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were conducted in the following countries: South Korea [ 23 , 24 ], France [ 25 , 26 ], Australia [ 27 , 28 ], Japan [ 9 , 29 ], the USA [ 30 , 31 ], Belgium [ 10 ], Mexico [ 11 ] and the Netherlands [ 14 ]. Papers were published between 1991 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Nine and four studies used cross-sectional and cohort design, respectively ( Table 1 ). Participants were enlisted from diverse settings: three studies recruited participants from communities [ 9 , 23 , 27 ]; four from long-term healthcare facilities [ 24 , 28 , 30 , 31 ]; five from hospitals, specifically from an acute geriatric department [ 10 ], geriatric rehabilitation centre [ 25 ] and geriatric department [ 14 , 26 , 29 ]; and the remaining from retirement homes and communities [ 11 ]. The inclusion and exclusion criteria varied across the included studies [ 9–11 , 14 , 23–31 ], and the sample sizes fluctuated between 50 and 1,308 cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research groups have found a more pronounced BP drop after high carbohydrate compared to high fat feeding, (1, 3, 5, 6, 10, 13, 14) and another study showed a sustained BP increase after high fat feeding (3, 6). However, one large study on a Mexican population found no correlation between macronutrient composition and PPH (4). One study found that warmer meals resulted in larger decreases in post-prandial blood pressure (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented in older adults (2–6) and can be accompanied by falls and syncope (7). Individuals with neurological diseases are at greater risk of PPH, including Alzheimer’s disease (AD), Parkinson’s disease and diabetic neuropathy (4, 810). Other risk factors include both hypertension (HTN) and severe hypotension (10, 11).…”
Section: Introductionmentioning
confidence: 99%